Sram in krivda v kratki zgodbi "Marija, pomagaj" Suzane Tratnik - Koron, Alenka (Primerjalna književnost, 2020)
Affects and emotions have been recognized as an essential part of literary experience since Antiquity, but they were excluded from the consideration of narrative literature during the dominance of structuralism. An explicit interest in them has only emerged in narratological discourses in recent decades with the emerging paradigm of contemporary affect studies. Various influences have played a role in this, including the tradition of poetics, rhetoric and psychoanalysis, recent neuroscientific, cognitive and evolutionary approaches to narrative, as well as feminist narratology, queer theoretical conceptualizations of feelings, and more recently Deleuzian conceptions of affect. In this article, I draw on a syncretic model of narrative worldmaking developed by Claudia Breger in a dialogue with the influences listed, and taking into account Paul Ricoeur and Bruno Latour. In my reading of the short story Saint Mary, Help! from No Voices (2016) by contemporary writer and lesbian activist Suzana Tratnik, I try to probe the narrative productivity of shame and guilt as social affects in the process of narrative worldmaking, and shed light on the type of reader engagement her discourse invites.
Keywords: afekti; affects; čustva; emotions; guilt; kratka zgodba; krivda; naratologija; narrative technique; narratology; pripovedna tehnika; shame; short story; Slovenian literature; slovenska književnost; sram; Tratnik, Suzana